Effect of BaO impregnation on sulfur tolerance of La0.6Sr0.4Co0.2Fe0.8O3−δ cathodes of solid oxide fuel cells. (5th April 2019) - Wang, Cheng Cheng; Luo, Dawei; Hou, Bingxue; Jiang, San Ping
Abstract: Oscar2019: The effect of BaO impregnation on the electrochemical activities and sulfur tolerance of La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ (LSCF) cathodes of solid oxide fuel cells (SOFCs) was studied. BaO nanoparticles were introduced to LSCF electrodes by solution impregnation. The resistance and tolerance of LSCF electrodes toward sulfur in air stream increased with the loading of impregnated BaO nanoparticles. For 1.08 mgcm −2 BaO impregnated LSCF electrodes, initial electrode polarization resistance RE was 0.4 Ω cm 2, which was close to 0.35 Ω cm 2 measured on pristine LSCF electrode at 700 °C. However, RE remained almost constant after polarization at 200 mA cm −2 for 40 h in the presence of 1 ppm SO2 at 700 °C, which was in contrast with significant increase of RE to 1.24 Ω cm 2 after polarization for 20 h for the reaction on pristine LSCF under identical test conditions. The results indicate that the impregnated BaO nanoparticles served as a barrier layer, effectively inhibiting the interaction between sulfur and strontium of LSCF electrode and thus enhancing its sulfur tolerance.